Maintenance management for government building (building under PDRM) / Nik Qhilman Alif Nik Mustapa - Nik Mustapa, Nik Qhilman Alif (2007)
PDRM mostly the biggest name in Malaysia, PDRM have major function to make sure that resident of the country were living lively and safety. From their mission and vision, the maintenance management should be programmed excellent into their organization, make the management complete and systematic because, if the PDRM management was in trouble, so how they want to manage and given their perfectionist situation to people out there. The maintenance management should be contributing into organization because the perfect organization can give the work program move smoothly. The research done to identifies the problem that always occurred in the PDRM management system. Research provides to known about the real situation in the PDRM and makes the compare with the program that PDRM planning Methodologies of the research to complete this dissertation were involved in 3 steps; firstly make the discussion with supervisor about the preparation in this dissertation. Secondly, list down the activity must be attached in this dissertation such as observation and questionnaires to get some data from occupier of quarters and employee of PDRM (staff). Lastly, make references from library, IPD and IPK to establish tough content of dissertation. Based on the 3 arrangement programmed, the finding were collected in negative feedback in programmed process but excellent in maintenance management programmed. The process negative because of the late in action process, so more complained from client make it negative feed back. But in other side, another programmed mostly in medium situation. The conclusion, PDRM mostly the biggest empire and they also have many programmed to make succeed, so the late feedback or action can be listed in relevant situation to compare with their situation, problem to handle and many more.